Experimental investigation of passive tuned mass damper and fluid viscous damper on a slender two dimensional steel frame - Gordan, Meisam (2014)
Vibration is a serious concern for tall buildings added to a natural disaster such as earthquake, wind storms, sea waves and hurricanes. The risk of occurrence of structural damage can be decreased by using a controlled vibration system to increase the damping characteristics of a structure. Damping is defined as the ability of the structure to dissipate a portion of the energy released during a dynamic loading event. The aims of this study are (1) to investigate a 4-storey 2D steel frame retrofit with tuned mass damper to reduce its vibration as well as compare the results with response displacement of the structure using viscous damper. In this project, the focus is limited to present an experimental model with semi-rigid connections and to show its validity by comparing the experimental results (achieved from shaking table test) with the analytical results obtained from theoretical model (SAP2000 software), (2) to demonstrate the performance of such a damper when fitted to a structure by analysis and tests the models and (3) comparison the dynamic responses of the structure in three verify of: a) using passive tuned mass damper, b) using viscous damper and c) using the combination of these two damping devices. Therefore, a series of shaking table tests of the 4-storey 2D steel frame with and without passive tuned mass damper (PTMD) and viscous damper (VD) was carried out to evaluate the performance of the buildings. The results of the experimental tests illustrate that damping devices decrease the structural responses of slender frame on shaking table. In addition, effectiveness of passive tuned mass damper is greater than viscous damper.